Comparison of UV-A photolytic and UV/TiO2 photocatalytic effects on Microcystis aeruginosa PCC7813 and four microcystin analogues: A pilot scale study. (15th November 2021) - Menezes, Indira; Capelo-Neto, José; Pestana, Carlos J.; Clemente, Allan; Hui, Jianing; Irvine, John T.S.; Nimal Gunaratne, H.Q.; Robertson, Peter K.J.; Edwards, Christine; Gillanders, Ross N.; Turnbull, Graham A.; Lawton, Linda A.
Abstract: To date, the high cost of supplying UV irradiation has prevented the widespread application of UV photolysis and titanium dioxide based photocatalysis in removing undesirable organics in the water treatment sector. To overcome this problem, the use of UV-LEDs (365 nm) for photolysis and heterogeneous photocatalysis applying TiO2 coated glass beads under UV-LED illumination (365 nm) in a pilot scale reactor for the elimination of Microcystis aeruginosa PCC7813 and four microcystin analogues (MC-LR, -LY, -LW, -LF) with a view to deployment in drinking water reservoirs was investigated. UV-A (365 nm) photolysis was shown to be more effective than the UV/TiO2 photocatalytic system for the removal of Microcystis aeruginosa cells and microcystins. During photolysis, cell density significantly decreased over 5 days from an initial concentration of 5.8 × 10 6  cells mL −1 until few cells were left. Both intra- and extracellular microcystin concentrations were significantly reduced by 100 and 92 %, respectively, by day 5 of the UV treatment for all microcystin analogues. During UV/TiO2 treatment, there was great variability between replicates, making prediction of the effect on cyanobacterial cell and toxin behavior difficult. Graphical abstract: Image 1 Highlights: UV-A photolysis was effective for elimination of cyanobacteria and toxins. Complete inhibition of M. aeruginosa PCC7813 by UV-A photolysis. 92 % removal of four microcystins after UV-A photolysis (intra- and extracellular). TiO2 photocatalysis was less effective in M. aeruginosa PCC7813 cell removal.